Authors' roundtable: scientific writing, peer review, and publication across journals. Issue 1 (1st June 2016) - Bradt, Joke; Baker, Felicity; Bergmann, Thomas; Bonde, Lars Ole; Clark, Imogen; Gold, Christian; Loewy, Joanne; McFerran, Katrina; Meadows, Anthony; Robb, Sheri; Vaillancourt, Guylaine; Alexis, ElisaBeth
Abstract : Background : Preparing a manuscript for submission and moving through the peer review process can be a challenging task. Authors may benefit from learning about the peer review process and understanding common pitfalls. Objective : Editors from music therapy journals across the globe will facilitate discussion with attendees about the process of peer review and scientific publication, offering cross-journal perspectives and examples from the vantage point of editor, reviewer, and author. Methods : Editors will present topics across six key areas: (1) overview of the review process, (2) strategies for preparing a strong manuscript, (3) common reasons manuscripts are declined publication, (4) how to respond to reviewer comments, (5) citation metrics and impact factor, and (6) ways editors/editorial boards can improve the peer review process for authors/reviewers. Emphasis is on facilitating dialogue among editors and session participants. Conclusions : This roundtable will provide transparency about the peer review process and guidance for the preparation of strong manuscripts.